District cooling pipes. Bonded single pipe systems for directly buried cold water networks. Factory made steel valve assembly for steel or plastic service pipe, polyurethane thermal insulation and a casing of polyethylene Part 3, (7th September 2021) - British Standards Institution,
No abstract available